Episthemological formulation of the Cartesian cogito (Andamios, Revista de Investigación Social, 2011)
The present work aims to look into the first philosophical certainty of René Descartes: the nature of cogito ergo sum. Initially, the skepticism in which Descartes is immersed is presented, and later we consider how is the: I think, I exist, trying to point out that the cogito is an inference.
Keywords: skepticism; res cogitans; Inference; mind; body